DEVELOPMENT OF SCIENTIFIC AND METHODOLOGICAL APPROACHES TO THE ORGANIZATION OF ESG ACTIVITIES OF ENTERPRISES - Tetіana M. Bolgar; Liubov F. Korchahina (Akademičnij Oglâd, 2024)
The article explores new models of the organization of the economy, called the circular economy – a model of production and consumption aimed at overcoming global challenges, such as climate change, loss of biodiversity, waste and environmental pollution. The participants were identified and the forms of participation in the process of achieving the SDGs (sustainable development goals) were defined. It was substantiated that the use of the principles of the UN Global Compact in the practical activities of enterprises should ensure that they comply with their basic duties to people and the planet, and would also create the foundations for long-term success. The types of ESG activity of enterprises were systematized according to certain criteria, followed by their classification and definition of the basic objects to which the ESG activity of the enterprise is directed. The standpoints of classical economics were analyzed, by studying the scientific works of specialists in this field of science. Based on the results of this analysis, it was established that ESG activity is a cost that with a doubtful probability can be compensated in the form of additional income. That is, by default it is a loss-making activity. At least, such a perception of ESG-activity can be when studying the issue superficially. The analysis of academic literature and corporate practice made it possible to highlight the key motives for enterprises to implement ESG activities. A study of ESG activity of Ukrainian enterprises was conducted and it was established that this process in Ukraine is at the stage of formation and the situation in this area has significantly worsened due to the war. According to the results of the study of the theoretical foundations of ESG activity of enterprises, the author’s interpretation of the term «ESG activity» was proposed, which should be understood as all types of enterprise activities aimed at achieving the goals of sustainable development through appropriate management decisions, which include measures to improve the environmental condition, social relations and corporate responsibility